TRANSFORMATION OF THE IMAGE OF RUSSIANS IN THE BRITISH MEDIA DISCOURSE (BASED ON THE MATERIAL OF THE BRITISH MEDIA 1941-1945 and 2014-2023) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-69-79The relevance of this article lies in the need to study the transformation of the image of Russians in the British media discourse during periods of allied relations between Russia and Britain and during periods of confrontation between these states, which is necessary to expand the understanding of the mechanisms of transformation of the image of ethnos in the political media discourse. The purpose of the article is a comparative analysis of the conceptual and linguistic-stylistic actualization of the images of Russians in the British media discourse during the Second World War and the last decade. The results of the research show that during the Second World War, when the Soviet Union and Britain were allies in the fight against Nazi Germany, the image of Russians had a positive connotative background. Its conceptual space included such axiologically significant concepts as "ally", "defence", "bravery", "courage", "battle", "sacrifice", "victory", "confidence", "unity" and "patriotism." Russians were attributed such positive personality qualities, represented in the conceptual space of the image by the corresponding concepts, as emotionality, a good sense of humor, complaisance, patience, cordiality Creating such an image, British journalists used functionalevaluative words of positive semantics, comparative constructions, allowing to show the constancy of positive qualities, and contrast, with which the bravery of Russian soldiers was emphasized in comparison with the nations that failed to resist fascism.Due to the confrontation between Russia and Britain that has intensified since 2014, the connotative background of the image of Russians is mostly very negative. The conceptual field of the image of Russians includes such axiologically significant concepts as "enemy", "crime", "prostitution", "corruption", "evil", "deceived by propa-ganda", "weakness", "fear", "despair" and "depression". This image is created with the help of evaluative and functional-evaluative lexemes with negative evaluation, com-parative constructions and metaphorical epithets.Key words: imagology, political modalization, political media discourse, image, stereotype, concept